Consumption of fresh or minimally processed foods and ultra-processed foods according to social vulnerability among Brazilian university students - José, Maria Eduarda Ribeiro; Oliveira, Natália; Perez, Patrícia Maria Périco; Rocha, Nayara Côrtes; Canella, Daniela Silva (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic worsened the diet quality of the population, including young adults, owing to the sudden economic insecurity caused by global chaos.ObjectiveTo describe the food consumption of students admitted to university after the pandemic, according to the social vulnerability situation.MethodsCross-sectional study conducted with students who were in a Brazilian public university located in Rio de Janeiro in 2022. Data collection was carried out online. Fresh or minimally processed foods and ultra-processed foods were assessed considering the consumption on the previous day and the regular intake (>5 days/week). To assess social vulnerability three indicators were used: the form of university admission, a socioeconomic score, and food (in)security.ResultsA total of 924 students participated in the study. Most of them were 18–22 years-old (50%), cisgender women (62%), of white people (53%), 30% were quota students, 32% had family income ranging between 2 to 5 minimum wages, and 36% were food insecure, with or without hunger. Consumption of fresh or minimally processed foods was more frequent among students with a higher socioeconomic score, non-quota students, and food-secure ones. Consumption of ultra-processed foods seems to have been less influenced by students’ social conditions in this sample of students.ConclusionThe food consumption, mainly related to fresh or minimally processed foods, was influenced by the vulnerability of university students. The findings reinforce the need for permanent student support policies, since universities can be strategic places to ensure the human right to adequate and healthy food.